Pengaruh Persiapan dan Meletusnya Perang Nuklear bagi Manusia dan Ekosystemnyau Nth: - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1987)
ABSTRACT T. Jacob. The impact of the preparation and outbreak of a nuclear war on man and his ecosystem This article described the medical effects of nuclear arms race and of a probable, intended, unintentional or self-ignited, nuclear war. The danger prior CO and after the explosion of the nuclear arsenal is brought forth. Among the post-war effects the global and prolonged ecological damages are elaborated, affecting both the physical-biological and cultural ecosystem. Considering these effects, post-war survival would not be preferable to immediate death. Medicine would be rendered impotent in such a nuclear holocaust